Arab Defamation Laws: A Comparative Analysis of Libel and Slander in the Middle East. Issue 2 (3rd April 2017) - Duffy, Matt J.; Alkazemi, Mariam
Abstract : Nations in the Arab world are known for their restrictions on press freedom, with public officials often using defamation laws to hinder good journalism. To promote reform, this article analyzes defamation laws of six Arab countries – Egypt, Jordan, Kuwait, Lebanon, Libya and the United Arab Emirates – and compares them to international norms. In areas with strong press protections, three characteristics related to defamation law were identified. First, defamation cases should be handled by civil lawsuits rather than police complaints, so journalists are not threatened with jail for their reporting. Second, the law must afford greater scrutiny for public figures than for private individuals so that the powerful cannot stifle public debate. Third, truth must be an absolute defense against allegations of defamation, so that people cannot protect an undeserving good reputation. The analysis reveals that defamation provisions in these countries are not in alignment with international norms.